Design of a landfill final cover system. Issue 3 (June 2010) - Stark, T.D.; Newman, E.J.
Abstract : ABSTRACT: This paper describes a final cover slope failure at a municipal solid waste containment facility. The lessons learned from this case history include: (i) slope stability analyses should be conducted whenever field conditions differ from initial design assumptions, such as a steeper slope and different geosynthetics; (ii) published values of interface strength/friction angle should not be used for final design, instead site-specific interface testing should be used; (iii) final cover slope angle should not exceed the lowest geosynthetic interface strength in the cover system to prevent tension in the geosynthetics and/or progressive slope failure of the slope; and (v) designers should resist the temptation to utilise a pre-existing final cover design without performing the necessary field reconnaissance, interface testing, analysis, and design for the new site.